3D imaging of moving targets for ultra‐wideband MIMO through‐wall radar system. Issue 3 (18th February 2021) - Pan, Jun; Ye, Shengbo; Shi, Cheng; Yan, Kun; Liu, Xin; Ni, Zhikang; Yang, Guangyao; Fang, Guangyou
Abstract: Ultra‐wideband (UWB) radar is widely used in static through‐wall imaging (TWI). There are still many imaging problems of motion through‐wall targets for complex system structure and unknown wall environment. Herein, a motion compensation method based on the reference channel and a modified Kirchhoff migration imaging algorithm are proposed for Ultra‐wideband (UWB) MIMO sparse array, which is used for high‐precision 3D TWI of moving targets. The channels of the MIMO radar are time‐division multiplexing based on microwave switch. Besides, a reference channel is added for motion compensation of moving targets. Performing motion compensation on the target before 3D imaging can effectively avoid the problems of defocus and position deviation caused by target motion. In the proposed imaging method, the backward Green function is used to replace the forward Green function to solve the problem of a large field of view with small arrays. The experiment with a static through‐wall target proves that the proposed imaging algorithm can suppress sidelobes well compared with the traditional back‐projection algorithm (BPA). Through‐wall experiments are carried out for targets with different speeds, and results show that the positioning accuracy and sidelobe level of the proposed compensation method is better than previously proposed methods.